2012
DOI: 10.1021/jm300822g
|View full text |Cite
|
Sign up to set email alerts
|

Design of Fully Synthetic, Self-Adjuvanting Vaccine Incorporating the Tumor-Associated Carbohydrate Tn Antigen and Lipoamino Acid-Based Toll-like Receptor 2 Ligand

Abstract: Overexpression of certain tumor-associated carbohydrate antigens (TACA) caused by malignant transformation offers promising targets to develop novel antitumor vaccines, provided the ability to break their inherent low immunogenicity and overcome the tolerance of the immune system. We designed, synthesized, and immunologically evaluated a number of fully synthetic new chimeric constructs incorporating a cluster of the most common TACA (known as Tn antigen) covalently attached to T-cell peptide epitopes derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Constructs incorporating a cluster of the most common tumor-associated carbohydrate antigens (known as Tn antigen) covalently attached to T cell peptide epitopes and LAA consisting of two 16-carbon lipoamino acids have been evaluated (108). These constructs induced potent antibody responses in mice without the need for an additional adjuvant, carrier protein, or special formulation (e.g., liposomes).…”
Section: Lipoamino Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructs incorporating a cluster of the most common tumor-associated carbohydrate antigens (known as Tn antigen) covalently attached to T cell peptide epitopes and LAA consisting of two 16-carbon lipoamino acids have been evaluated (108). These constructs induced potent antibody responses in mice without the need for an additional adjuvant, carrier protein, or special formulation (e.g., liposomes).…”
Section: Lipoamino Acidmentioning
confidence: 99%
“…These constructs induced potent antibody responses in mice without the need for an additional adjuvant, carrier protein, or special formulation (e.g., liposomes). Structure-activity studies demonstrated that linear or branched vaccine architecture had a significant effect on antibody recognition (108). …”
Section: Lipoamino Acidmentioning
confidence: 99%
“…For example, Pam3CSK4 enhanced CD8 + regulatory T cell (T reg ) survival (105). Interestingly, glycolipopeptide constructs can be used to design composite tumor vaccines (106). These compounds contain carbohydrate antigens, CD4 + or CD8 + T cell epitopes, and TLR2 stimulating lipid chains.…”
Section: Therapeutic Potential Of Tlr2 Signaling Plasticitymentioning
confidence: 99%
“…[36] The development of less toxic adju-vants and self-adjuvanting multi-componentv accines has also been investigated,r esulting in remarkable immunological effects. [37][38][39][40][41][42][43][44][45] Finally,w hen many structures only present the carbohydrate moiety of the TACA instead of the native glycopeptide antigen, more relevant results have been obtained compared to when the TACA are linked to an amino acid of the native peptide fragment. [30,[46][47][48] However,d espite thesei mportant improvements, no carbohydrate-based antitumor synthetic vaccine has succeeded in clinical trials.…”
Section: Introductionmentioning
confidence: 99%